Survei Kepuasan Masyarakat (Skm) Manfaat Pemberian Laptop Untuk 1 Rt Di Kabupaten Kutai Kartanegara Tahun 2020 - Akbar, Ali; Sundoyo, Sundoyo (FAKULTAS EKONOMI DAN BISNIS UNIKARTA, 2021)
Abstract: This study aims to determine the level of performance and level of satisfaction of Neighbourhood (RT) services in Kutai Kartanegara Regency. Respondents in this research are the people or residents who have done management or who have received public services to the Head of the RT in the Tenggarong sub-district, as many as 207 respondents. The analytical method used is descriptive analysis. The results showed that the cumulative achievement of the IKM measurement results was 74.99. This means that in general the implementation of the program of providing 1 (one) Laptop 1 (one) Neighbourhood (RT) in Tenggarong District by the Population and Civil Registration Service of Kutai Kartanegara Regency according to Permen PAN RB No. 14 of 2017 is classified as unfavorable. Of all the elements and service areas according to Permen PAN RB No. 14 of 2017 in the unfavorable category has a range of values (65.00 - 76.60), which can be described as follows: Service Procedure (76.33), Service Time (72.28), Product service specifications (74.28), Executive Competence (73,31), Complaint Handling Services (73,13), Infrastructure (74.11). Keywords: Service Quality, Community Satisfaction